Level of Motivation of Beef Cattle Farmers (Case Study of the "Mammesa" Livestock Farmers Groups in Duampanua District, Pinrang Regency - Ismail S; Angga Nugraha; Armayani M (International Journal of Sustainable Applied Sciences, 2023)
The aim of this research was to determine the level of motivation of beef cattle breeders in the Mammesa Farmer/Livestock Group in Data Village, Duampanua District, Pinrang Regency. This research method uses quantitative with Likert scale measurements. The results of the overall level of motivation in Data Village, Duampanua District, Pinrang Regency, with a total weight of 2,395, which differs between the needs of "Strongly agree" and "Agree", namely between 625 to 3,125. This can be categorized as "Agree" because breeders are aware that raising livestock can increase the opinion and experience of the level of motivation of beef cattle breeders in Data Village, Duampanua District, Pinrang Regency. Obtaining the Agree category in five levels of needs including Physiological needs, security needs, social needs, self-esteem needs, and self-actualization needs. This can be seen from the total weight of 2,395 which shows that raising beef cattle can fulfill physiological needs, the need for security, social needs, the need for self-esteem, and the need for self-actualization.